Тенденции развития преобразователей частоты с учетом совершенствования элементной базы - Колот, Александр Владимирович; Квашнин, Валерий Олегович; Копа, Ирина Анатольевна (НТУ "ХПИ", 2010)
There are the modern directions of the development converters` technology of the AC motor drive. There is the review of the topology matrix converter, its advantages compared to double-link frequency converter. There are the results of the modeling converter with inverter and matrix converter. The questions of advantages of the matrix drive and the perspective of its application are shown.
The tendencies of the development frequency converters according to the enhancement of element base
Keywords: электропривод; ротор; транзистор; полупроводник; ток переменный; преобразователь матричный; модуляция широтно-импульсная; автономный инвертор напряжения; нагрузка; MatLab Simulink; напряжение выходное; ключ двунаправленный